Proposed new interior design and schemes for Mini Cooper Showroom (Auto Bavaria) Malaysia at Lot 137, Jalan Sultan Ismail Kuala Lumpur / Shaiful Ezhan Kamaruddin - Kamaruddin, Shaiful Ezhan (Faculty of Architecture, Planning and Surveying, 2006)
The main objectives of this project is to proposed a new interior design for MINI Cooper Malaysia (Auto Bavaria) Showroom and Sales Center as a part of its under oneroof marketing vehicle in Malaysia and to develop a design scheme that would express its corporate identity as a well-established leader in an automotive industry in Malaysia. It is a challenge to design a car showroom which tried to explore new methods in displaying cars with an out of the box approach. This project offers a comprehensive range of facilities and professional sen/ices which are rendered according to the guideline set-up by the client’s. A series of interview and observation had been conducted in order to collect relevant data and information. A set of sample (questionnaires) had been distributed to various target group such as public, MINI Cooper car owners and automotive - link companies. Based on the case study and observation, I can conclude that it is vital to create a showroom space which fulfill the client requirements and adapting appropriate design concept and schemes in order to enhance the success of the organization itself. Beside that, it is also essential for the showroom to be the a space that is compelling and inviting because the main point of the building itself is to sell. The finding of this research shown that it needs to be commercialized and to cater for the public as well as the MINI lovers. It will also gives an advantage to dealer to expose the new MINI Cooper product to the customers. To achieve a high quality of MINI Cooper Showroom, we specified the design according to the guideline of Auto Bavaria Malaysia. Share the experience most incredible MINI Cooper that perhaps one day will be one of the best selling car in Malaysia.